2020
DOI: 10.3390/cancers12030619
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Efficacy of Oncolytic Adenoviruses In Vitro and In Vivo: Current and Future Perspectives

Abstract: Oncolytic adenoviruses (OAd) selectively target and lyse tumor cells and enhance antitumor immune responses. OAds have been used as promising cancer gene therapies for many years and there are a multitude of encouraging pre-clinical studies. However, translating OAd therapies to the clinic has had limited success, in part due to the lack of realistic pre-clinical models to rigorously test the efficacy of OAds. Solid tumors have a heterogenous and hostile microenvironment that provides many barriers to OAd trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…The ability of the combination treatment using oncolytic viruses with pembrolizumab to enhance anti-cancer potency and induce immunogenic cell death were investigated in vivo. To this aim, we used the C57BL/6 as the immunocompetent mouse model rather than immunodeficient xenograft alternative models [ 53 ] since we aimed to elucidate the involvement and contribution of the immune system to the efficacy of our combination therapy. Syngeneic tumor models (C57BL/6 or BALB/c mice) are the oldest and most commonly utilized preclinical models to evaluate anticancer therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the combination treatment using oncolytic viruses with pembrolizumab to enhance anti-cancer potency and induce immunogenic cell death were investigated in vivo. To this aim, we used the C57BL/6 as the immunocompetent mouse model rather than immunodeficient xenograft alternative models [ 53 ] since we aimed to elucidate the involvement and contribution of the immune system to the efficacy of our combination therapy. Syngeneic tumor models (C57BL/6 or BALB/c mice) are the oldest and most commonly utilized preclinical models to evaluate anticancer therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive immunohistochemical analysis revealed upregulated expression of PSMA on malignant prostatic epithelia and undetectable levels in normal tissues . The uptake study and selective internalization of bioconjugate 12 in PSMA + LNCaP cells are shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“…Estimates suggest that >80% of biologists rely on two-dimensional (2D) culture assays prior to in vivo testing because of their convenience, simplicity, and accessibility . Advantages of employing three-dimensional (3D) culture models over 2D culture include (i) increased interactions between cells and extracellular matrix, (ii) study of site-specific stromal cells in tumor microenvironments, (iii) study of varying cell proliferation zones, and (iv) establishment of oxygen, nutrient, metabolites, and catabolite gradients mimicking the solid tumor environment. , Image-guided tracking of diagnostics in 3D tumor models is a major medical need as it enables the study of the movement of fluorophores in real time .…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies on adenoviral vectors in general and their use in vaccine- and gene therapy approaches in particular have been extensively reviewed. The same applies to oncolytic adenoviruses in animal models that are not part of this work, but were reviewed by others recently [ 8 , 9 , 10 , 11 , 12 ]. This review outlines the current knowledge on HAdV susceptibility of different animal models, highlighting key features, strengths, and limitations.…”
Section: Introductionmentioning
confidence: 94%